Clinical characteristics and outcomes after bowel surgery and ostomy formation at the time of debulking surgery for advanced-stage epithelial ovarian carcinoma. (March 2019) - Gockley, Allison Ann; Fiascone, Stephen; Hicks Courant, Katherine; Pepin, Kristen; Del Carmen, Marcela; Clark, Rachel M; Goldberg, Joel; Horowitz, Neil; Berkowitz, Ross; Worley Jr, Michael
Abstract : Objective: There are limited data on clinical outcomes of patients with advanced-stage epithelial ovarian cancer who require ostomy formation at the time of either primary cytoreductive surgery or interval cytoreductive surgery. The objective of this study was to evaluate patients undergoing bowel surgery and ostomy formation after primary or interval surgery. Methods: Patients with International Federation of Gynecology and Obstetrics (FIGO) stage IIIC-IV epithelial ovarian cancer who underwent cytoreductive surgery between January 2010 and December 2014 were identified retrospectively. Patients with non-epithelial histology, low-grade serous histology or incomplete medical records were excluded. Demographic and clinical data were collected and analyzed. Age, stage, co-morbidity index, pre-operative CA125, pre-operative albumin, and Aletti surgical complexity score were included in a multivariable logistic regression model to assess independent associations with ostomy formation. Results: A total of 554 patients were included in the study. Of these, 261 (47%) underwent primary cytoreduction and 293 (53%) underwent interval cytoreduction. Patients undergoing primary surgery were more likely to undergo bowel resection, compared with interval surgery patients (37.2% vs 14%, p<0.001). Of the 139 (25.1%) patients who underwent bowel surgery, 25 (18%) underwent ostomy formation (11 ileostomies and 14 colostomies). Rates of ostomy formation were similar between the groups (6.1% primary vs 3.1% interval, p=0.10). Patients undergoing ostomy formation were more likely to have longer mean operative time (335 vs 229 min, p<0.001) and undergo small and large bowel resections at the time of cytoreductive surgery (44% vs 14%, p<0.001). Multivariate analysis revealed that a high surgical complexity score was associated with ostomy formation. Of the patients who underwent ostomy formation, 13 (43.3%) underwent stoma reversal including 11 ileostomies and two colostomies. Median time to ostomy reversal was 7 months. Conclusion: Bowel surgery is more common among patients undergoing primary surgery as compared with interval surgery, but this does not result in an increased risk of ostomy formation.